To fight poverty and social exclusion, EU law must buttress basic nuts and bolts of the welfare edifice. Issue 4 (December 2020) - Vandenbroucke, Frank
This article provides a conclusion to the EJSS Special Issue 'Discussing strategies for Social Europe: The potential role of EU law in contributing to the Union's policy objective of fighting poverty and social exclusion'. The contributions to this Special Issue raise a fundamental question: why did European governments fail to deliver on their promise, proclaimed with so much emphasis twenty years ago, to reduce poverty in Europe? It is too easy to say that the one and only problem was the non-binding nature of the social objectives of Lisbon and the antipoverty targets of Europe 2020 . There is a broader challenge at the EU level, which goes beyond minimum income protection and directly involves crucial nuts and bolts of the whole welfare edifice: when confronted with severe economic and social shocks, welfare states need an adequate stabilization capacity. This implies that the European Monetary Union becomes a true 'insurance union'. I argue that one should understand the relevance of the European Pillar of Social Rights from this perspective, and I relate that argument to the contributions to the Special Issue.